THE EFFECT OF UTAZI LEAFE ETHANOLIC EXTRACT ON THE PROXIMATE ANALYSIS OF Clarias gariepinus FINGERLINGS EXPOSED TO DICLOFENAC - Okoh, Emmanuel Chidera; Orji, Alexander Emeka; Isife, Paschaline Nmesoma (Global Journal of Medical and Health Science, 2025)
This study investigated the protective effects of Gongronema latifolium (Utazi leaf) ethanolic extract on the proximate composition of Clarias gariepinus fingerlings exposed to diclofenac, a commonly used nonsteroidal anti-inflammatory drug (NSAID) known for its environmental toxicity. The phytochemical analysis of utazi leaf was conducted, and the quantitative analysis showed that tannins, quinones, and flavonoids had high ethanol constituents (10mg/100g, 9.4mg/100g, and 7.24mg/100g respectively) and alkaloid and tannins having higher aqueous constituent (13.4mg/100g, and 12.4mg/100g respectively). The fingerlings were divided into four groups: the control, diclofenac-only, extract-only, and combined diclofenac and extract groups. Proximate analysis of the fish was conducted to determine the moisture, crude protein, crude fat, and ash contents. Results indicated that diclofenac exposure significantly reduced crude protein content from 17.93±0.057 in the 6% ULE group, decreasing in all groups, stabilizing around 9-10% at 28 days, and increasing lipid peroxidation, thereby compromising the nutritional quality of the fish. However, fish treated with Gongronema latifolium ethanolic extract showed a marked improvement in these parameters, suggesting that the extract effectively mitigates the oxidative stress and protein degradation caused by diclofenac. These findings highlight the potential of Gongronema latifolium as a natural aquaculture additive that enhances fish health and nutritional value, especially in environments contaminated with pharmaceuticals. Further research is recommended to explore the long-term effects and underlying mechanisms of this protective action